Effects of the GLP-1 Receptor Agonist Dulaglutide on the Structure of the Exocrine Pancreas of Cynomolgus Monkeys. (October 2015) - Vahle, John L.; Byrd, Richard A.; Blackbourne, Jamie L.; Martin, Jennifer A.; Sorden, Steven D.; Ryan, Thomas; Pienkowski, Thomas; Rosol, Thomas J.; Snyder, Paul W.; Klöppel, Günter
Clinical and nonclinical studies have implicated glucagon-like peptide-1 (GLP-1) receptor agonist therapy as a risk factor for acute pancreatitis in patients with type 2 diabetes. Therefore, it is critical to understand the effect that dulaglutide, an approved GLP-1 receptor agonist, has on the exocrine pancreas. Dulaglutide 8.15 mg/kg (approximately 500 times the maximum recommended human dose based on plasma exposure) was administered twice weekly for 12 months to cynomolgus monkeys. Serum amylase and lipase activities were measured and 6 sections of each pancreas were examined microscopically. Ductal epithelial cell proliferation was estimated using Ki67 labeling. Dulaglutide administration did not alter serum amylase or lipase activities measured at the end of treatment compared to control values. An extensive histologic evaluation of the pancreas revealed no changes in the acinar or endocrine portions and no evidence of pancreatitis, necrosis, or pancreatic intraepithelial neoplasia. An increase in goblet cells noted in 4 of the 19 treated monkeys was considered an effect of dulaglutide but was not associated with dilation, blockage, or accumulation of mucin in the pancreatic duct. There was no difference in cell proliferation in ductal epithelium between control and dulaglutide-treated monkeys. These data reveal that chronic dosing of nondiabetic primates with dulaglutide does not induce inflammatory or preneoplastic changes in exocrine pancreas.